2007
DOI: 10.1073/pnas.0705794104
|View full text |Cite
|
Sign up to set email alerts
|

Toxofilin from Toxoplasma gondii forms a ternary complex with an antiparallel actin dimer

Abstract: Many human pathogens exploit the actin cytoskeleton during infection, including Toxoplasma gondii, an apicomplexan parasite related to Plasmodium, the agent of malaria. One of the most abundantly expressed proteins of T. gondii is toxofilin, a monomeric actin-binding protein (ABP) involved in invasion. Toxofilin is found in rhoptry and presents an N-terminal signal sequence, consistent with its being secreted during invasion. We report the structure of toxofilin amino acids 69 -196 in complex with the host mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Actin's natural tendency to polymerize constitutes an obstacle to crystallization. Different approaches have been used to overcome this problem, including the crystallization of complexes of actin with actin-binding proteins (ABPs) (20,(22)(23)(24)(25)(26) and toxins (27), and blocking actin polymerization by mutagenesis (28) or chemical cross-linking (29). We chose to attempt Author contributions: E.D.K.…”
Section: Resultsmentioning
confidence: 99%
“…Actin's natural tendency to polymerize constitutes an obstacle to crystallization. Different approaches have been used to overcome this problem, including the crystallization of complexes of actin with actin-binding proteins (ABPs) (20,(22)(23)(24)(25)(26) and toxins (27), and blocking actin polymerization by mutagenesis (28) or chemical cross-linking (29). We chose to attempt Author contributions: E.D.K.…”
Section: Resultsmentioning
confidence: 99%
“…This protein caps microfilaments and binds globular actin, making it unavailable for microfilament (re)polymerization [51]. The newly available crystal structure [52] showing that toxofilin uses several α-helices to embrace a host actin dimer should be invaluable for designing mutants to test its role in cortical cytoskeleton traversal.…”
Section: Cytoskeleton and Lysosomesmentioning
confidence: 99%
“…n$18 cells for each condition, with a minimum of 450 measurements per condition. exposed in the actin filament (Lee et al, 2007). Because the highly conserved Ras-GAP family member Aip1 has a binding site that has been mapped to this cleft and cooperates with cofilin to regulate actin turnover (Rodal et al, 1999;Ono, 2003), we checked whether toxofilin could similarly act by cooperating with cofilin/actin depolymerizing factor (ADF) in the host cells.…”
Section: Toxofilin Upregulates Actin Turnover Independently Of Host Cmentioning
confidence: 99%
“…Analysis of the atomic structure of the toxofilin -G-actin complex revealed that toxofilin, which is made up of five helices, binds to the actin nucleotide at residue Gln134 in helix 4, and that one toxofilin molecule interacts with two actin molecules organized as an antiparallel dimer. Although toxofilin appears to be a potent actin nucleotide-exchange inhibitor (Lee et al, 2007), its function in vivo remains undefined.…”
Section: Introductionmentioning
confidence: 99%